The Role of Gut Microbiota as a Trigger for Exacerbations in Pulmonary Obstruction Disorder in General - Wijaya, Dewi; Simatupang, Elvando Tunggul Mauliate; Putri, Yolanda Julia Perel; Pratiwi, Adelia; Anggraini, Dewi; Syam, Shaogi (Jurnal Respirasi, 2024)
Pulmonary diseases can be associated with the gastrointestinal (GI) system, particularly if an infection causes them. This relationship between organs is known as the gut-lung axis (GLA). Skin and mucosal surfaces are associated with microbiota (bacteria, fungi, viruses, macrophages, archaea, protists, helminths), which can trigger an immune response in GLA and serve a role in respiratory diseases. For instance, asthma can be inhibited by a specific antigen that is triggered by probiotics, the microorganisms found in the GI tract. Asthma incidence can be reduced by consuming fiber due to its ability to protect airways from infection. Pattern recognition receptors (PRRs) are the first immune component to identify microbial compounds in GI and lung epithelial cells. The PRRs then induce regulatory T-cell (T-reg) and Th-17 differentiation. Diet, antibiotics, and stress can all influence the structure and function of bacteria. This is known as dysbiosis. Lung microbiota can influence immune cell maturation and homeostasis. If the diversity of lung microbiota decreases, it will affect intestinal microbiota and may result in chronic respiratory disorders such as chronic obstructive pulmonary disease (COPD), asthma, and cystic fibrosis. This literature review explained how the interactions between the intestines and lungs can affect humans’ health and well-being.